INNOVATIVE COFFEE PACKAGING DESIGN TRAINING AS A SALES INCREASE STRATEGY IN TORAJA - Oktafianus, Sion; Galla, Ernytha; Swarno, Sakti; Kolo, Maria Asensao (Yayasan Literasi Kita Indonesia, 2024)
The coffee industry in Tana Toraja, known for its unique and high-quality coffee, is a critical component of the local economy. However, the effectiveness of coffee sales can be significantly influenced by packaging design, which plays a crucial role in attracting consumers and differentiating products in a competitive market. This study explores the educational needs and strategies for improving coffee packaging design among local producers in Tana Toraja. The research identifies key areas where packaging design can be enhanced to boost market appeal, including aspects such as branding, visual aesthetics, functionality, and sustainability. Despite the rich tradition of coffee production in Tana Toraja, many local producers lack specialized knowledge in contemporary packaging design techniques that can elevate their product's market presence. To address this gap, the study proposes a comprehensive educational program focused on coffee packaging design. This program includes workshops, training sessions, and digital resources tailored to the specific needs of Tana Toraja's coffee producers. The curriculum covers essential topics such as design principles, consumer psychology, effective branding strategies, and sustainable packaging materials. By equipping local coffee producers with the skills and knowledge to create attractive and functional packaging, the study aims to enhance their market competitiveness and contribute to the broader goal of economic development intheregion.Thefindingssuggestthattargetededucationinpackagingdesign can lead to improved sales performance and a stronger market presence for Toraja coffee, benefiting both producers and the local economy.This study underscores the importance of integrating packaging design education into the coffee production process to maximize the commercial potential of Tana Toraja's esteemed coffee products.